Project-Based Educational Technology as a Method for Developing Social Activity of Students (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Social activity and socialization of youth play an important role in society. Especially for female students, socialization is of great importance in strengthening their position in society, personal and professional development. In this article we will study the meaning, features and conditions of using project-based educational technologies in the socialization of female students and their role in increasing their social activity.